2020
DOI: 10.17323/2500-2597.2020.4.10.19
|View full text |Cite
|
Sign up to set email alerts
|

Technology Foresight and Sustainable Innovation Development in the Complex Dynamical Systems View

Abstract: Information and communication technologies (ICT) which are transforming most areas develop non-linearly. Failure to take into account the nonlinear principles of complex dynamic systems hinders development of balanced innovation strategies. Companies and governments lose the ability to effectively respond to “grand challenges”. The linear approach does not allow covering a wide range of critical areas simultaneously in the scope of Foresight projects, prevents from applying an interdisciplinary approach to dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 21 publications
0
14
0
1
Order By: Relevance
“…It has been established that high-tech development in a crisis and taking into account the standard understanding of VUCA factors of the external environment are effective when integrating their characteristics to better account for the resources of the knowledge economy. This is numerically confirmed by the correlation between managerial competencies, the quality of knowledge management and creative thinking by modeling the processes of effective functioning of knowledge networks in a number of studies [5,31,35,36]. Estimates of the foresight of future employment in the field of science, technology and innovation as a spiral of innovation in various configurations of the "knowledge triangle" were obtained [25,[35][36][37].…”
Section: Methods Of High-tech Development Of Enterprises In Terms Of ...mentioning
confidence: 84%
See 1 more Smart Citation
“…It has been established that high-tech development in a crisis and taking into account the standard understanding of VUCA factors of the external environment are effective when integrating their characteristics to better account for the resources of the knowledge economy. This is numerically confirmed by the correlation between managerial competencies, the quality of knowledge management and creative thinking by modeling the processes of effective functioning of knowledge networks in a number of studies [5,31,35,36]. Estimates of the foresight of future employment in the field of science, technology and innovation as a spiral of innovation in various configurations of the "knowledge triangle" were obtained [25,[35][36][37].…”
Section: Methods Of High-tech Development Of Enterprises In Terms Of ...mentioning
confidence: 84%
“…Separate use of foresight and controlling subsystems of enterprise development trends and the possibility of using the criterion of sustainability of high-tech development in knowledge economy systems were present, but there were no specific functions for integrating and combining resources of knowledge economy objects consistent with standard enterprise management functions. Mainly financial models of evolutionary increases in innovativeness of development based on foresight management in the "triangle of knowledge" or controlling strategic goals have been developed, and principles of building a controlling system and evaluating its effectiveness have been proposed [1][2][3][4][5][6]14,[23][24][25][26][27][28][29][30][31][32][33] and appeared, increasing the cyclical and strategic opportunities for improving the quality of managing the forecasting and for controlling the environment. The use of convergent models of cross-functional integration of enterprises with objects of the knowledge economy and the possibility of achieving stability in bifurcation processes of increasing the efficiency of innovative development were present, but the control subsystem of the enterprise and the complex became more complicated.…”
Section: Methods Of the Theory And Methodology Of Managing The Integr...mentioning
confidence: 99%
“…The main theme emerging within in this quadrant is "Complex Technological Solutions," which comprises research topics such as complex dynamic systems, complex structure management, cyber-physical systems, and foresight as the key terms. The principal argument within this research is that solutions to nonlinear and complex problems can solely be found by creating systems built on dynamic complexity and nonlinearity principles (Mainzer, 2020). This theme also includes research that revolves around the research question of how foresight, as a communication platform, can help solve grand challenges (Gokhberg et al, 2017).…”
Section: Peripheral Themesmentioning
confidence: 99%
“…In addition, it is necessary to take into account possible unforeseen circumstances ("dark corners" [1]) that require improved management in the digital economy in favor of structural changes, including the capital structure of the enterprise. The process of digitalization itself is not always carried out "as planned"; it was assumed that digitalization would develop exponentially [2], become more active as the scale increases, but this did not happen; digital technologies are used quite actively by organizations and households (judging by statistical reporting and analytics), but the effectiveness of digitalization is still low. Process measurement tools are always important in management, perhaps in this case it is necessary to change the tools for measuring the effectiveness of digitalization?…”
Section: Introductionmentioning
confidence: 99%